Т.ҚАЙЫПБЕРГЕНОВТЫҢ «УЙҚЫСЫЗ ТҮНЛЕР» ПОВЕСТИНДЕ ИНСАНЫЙЛЫҚ ХАРАКТЕРИНИҢ СҮЎРЕТЛЕНИЎИ - Сарсенбаев, Қ.Ж. (FAN va JAMIYAT, 2024)
The article discusses the writer's skillful use of artistic details and motifs in his works. When revealing the character of the writer, the essence of the details was taken into account.